Access to assisted reproductive technologies the case of France and Belgium - Merchant, Jennifer (Fertility, reproduction, and sexuality ;, 2020)
"Despite France and Belgium sharing and interacting constantly with similar culinary tastes, music and pop culture, access to Assisted Reproductive Technologies are strikingly different. Discrimination written into French law acutely contrasts with non-discriminatory access to ART in Belgium. The contributors of this volume are social scientists from France, Belgium, England and the United States, representing different disciplines: law, political science, philosophy, sociology and anthropology. Each author has attempted, through the prism of their specialties, to demonstrate and analyse how and why this striking difference in access to ART exists"--